A COMPARATIVE ANALYSIS OF UZBEK AND ENGLISH PROVERBS: CULTURAL INSIGHTS AND LINGUISTIC FEATURES - Axmedov, Ikboljon (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This study explores the similarities and differences between Uzbek and English proverbs, focusing on their cultural and linguistic dimensions. Proverbs serve as repositories of collective wisdom, reflecting societal values, historical contexts, and linguistic structures. By examining selected proverbs from both languages, this research uncovers the shared human experiences they embody, alongside the unique cultural and linguistic traits each represents. The findings highlight how proverbs function as cultural artifacts, providing insights into the traditions, beliefs, and communicative practices of Uzbek and English-speaking societies.